2022
DOI: 10.4018/978-1-7998-9795-8.ch009
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Systems in Latest DFA Compression Methods for DPC

Abstract: The vast majority of the system security application in today's systems depend on deep packet inspection. In recent years, regular expression matching has been used as an important operator that examines whether or not the packet's payload can be matched with a group of predefined regular expression. Regular expressions are parsed using the deterministic finite automata representations. Conversely, to represent regular expression sets as DFA, the system needs large amount of memory, an excessive amount of time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…First, an autoencoder (AE) is trained to compress bits of raw audio into an easier representation to process and to invert this representation into an audio signal (i. e., vocoder). For instance, mel-spectrogram representations were often used (e. g., [28]) before being replaced by more recent socalled neural codecs -as Soundstream [32], Encodec [33] or DAC [34] -that demonstrated better reconstructions. For interested readers, the latter commonly employ discretised latent spaces as codebooks of tokens -e. g., Residual Vector Quantization (RVQ) [35].…”
Section: Proposed Frameworkmentioning
confidence: 99%
“…First, an autoencoder (AE) is trained to compress bits of raw audio into an easier representation to process and to invert this representation into an audio signal (i. e., vocoder). For instance, mel-spectrogram representations were often used (e. g., [28]) before being replaced by more recent socalled neural codecs -as Soundstream [32], Encodec [33] or DAC [34] -that demonstrated better reconstructions. For interested readers, the latter commonly employ discretised latent spaces as codebooks of tokens -e. g., Residual Vector Quantization (RVQ) [35].…”
Section: Proposed Frameworkmentioning
confidence: 99%
“…Since DFA has the fantastical time complexity of O(1), a variety of studies [14]- [20] concentrate on trying to reduce the memory usage of DFA to support large-scale regex rulesets. These studies have found that the state transition table of DFA is sparse and propose various compression methods accordingly.…”
Section: A Software Rem Schemesmentioning
confidence: 99%